2017
DOI: 10.1186/s12870-017-1167-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping of black point reaction in common wheat (Triticum aestivum L.)

Abstract: BackgroundBlack point is a serious threat to wheat production and can be managed by host resistance. Marker-assisted selection (MAS) has the potential to accelerate genetic improvement of black point resistance in wheat breeding. We performed a genome-wide association study (GWAS) using the high-density wheat 90 K and 660 K single nucleotide polymorphism (SNP) assays to better understand the genetic basis of black point resistance and identify associated molecular markers.ResultsBlack point reactions were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
88
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 72 publications
(98 reference statements)
14
88
1
3
Order By: Relevance
“…Even though most studies have reported that LD decays slower for the D genome (e.g. Chen et al , ; Liu et al , ; Lopes et al , ; Sukumaran et al , ), there have been also some studies showing LD decay values for the D genome that are similar to or even lower than those of the A and/or B genomes (Sehgal et al , ; Zhang et al , ). One possible explanation for this discrepancy are the differences in number of marker pairs as a function of physical distance observed in our study (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…Even though most studies have reported that LD decays slower for the D genome (e.g. Chen et al , ; Liu et al , ; Lopes et al , ; Sukumaran et al , ), there have been also some studies showing LD decay values for the D genome that are similar to or even lower than those of the A and/or B genomes (Sehgal et al , ; Zhang et al , ). One possible explanation for this discrepancy are the differences in number of marker pairs as a function of physical distance observed in our study (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…The diverse panel of 166 varieties of wheat ( Triticum aestivum L.)was used in the present study, comprising 144 accessions from the Yellow and Huai River Valleys Facultative Wheat Region of China, and 22 accessions from other foreign countries, including Italy, Argentina, Japan, Australia and Turkey (Liu et al, ). The 166 wheat accessions were grown at Anyang in Henan Province (2013–2014 cropping season, named as Anyang 2013), Beijing (2015–2016 cropping season, named as Beijing 2016) and Gaocheng of Hebei Province (2015–2016 cropping season, named as Gaocheng 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Population structure, principal components analysis (PCA) and neighbour‐joining (Figure S2) tree analysis had also been conducted. The results indicated that the 166 wheat accessions could be divided into three subgroups (Dong et al, ; Liu et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal K-value was determined using the ΔK method [55].Linkage disequilibrium (LD) among markers was computed by the full matrix and sliding window options in Tassel v5.0 with the filtered SNP markers. The pairwise LD between the markers was calculated using squared allele frequency correlations r 2 , according to Liu et al [56].…”
Section: Population Structure Analysis and Linkage Disequilibriummentioning
confidence: 99%